The Influence of Government Expenditures on the Human Development Index With Gross Domestic Product As A Moderating Variable - Rizal R. Manullang; Ellyana Amran; Heppi Syofya; Iwan Harsono; Awalauddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Researchers believe that government spending that is good, measurable, based on research, efficient and effective can increase the Human Development Index in terms of improving the quality of education, quality of health and other things which in the end can have a good impact on the Human Development Index. Therefore, this research aims to analyze the influence of government spending on the Human Development Index. Different from previous studies, this research adds the Gross Domestic Product variable as a moderating variable which is believed to strengthen the influence of the Independent variable on the Dependent variable. This research is quantitative research with an explanatory approach which uses previous research as a benchmark/reference for finding new variations. The data used in this research is secondary data originating from the annual report of the Central Statistics Agency from 2018-2023. The data used in this research were analyzed using the smart PLS 4.0 analysis tool. The result in this research show the Government Expenditure variable can have a positive relationship and a significant influence on the Human Growth Index variable because the P-Values value is positive and is below the significance level of 0.05, namely 0.023. Apart from that, researchers also believe that the Gross Domestic Product variable can strengthen the influence of the Government Expenditure variable on the Human Growth Index. The researcher's confidence can be proven from the results of the second row of the third table of the Path Coefficient which shows the direction of a positive relationship and a significant influence. This is indicated by the results of the second line of the Path Coefficient which shows that the P-Values value is below the 0.05 significance level, namely 0.023. This means that the Gross Domestic Product of each province in Indonesia is good, continues to be stable, and even continues to increase every year, which can make the influence of the government budget and government expenditure stronger so that it has a good impact on the Human Growth Index. Thus, the first and second hypotheses in this study can be accepted.